292 The Impact of Hypothermia on Post-Natal Blood Biomarkers of Neonatal Hypoxic Ischaemic Encephalopathy. (October 2012) - Walsh, BH; Boylan, GB; Dempsey, EM; Murray, DM
Abstract : Numerous post-natal biomarkers of hypoxic ischaemic encephalopathy (HIE) severity have been proposed before the era of hypothermia. It is unclear if hypothermia impacts upon these potential biomarkers, and therefore whether previous findings are now valid. The aim of this study was to determine if hypothermia alters the discriminative ability of post-natal nucleated red blood cells (NRBCs) to distinguish between mild and moderate/severely encephalopathic infants. Methods: A prospective cohort study recruited term infants with HIE. The grade of HIE was categorised using Sarnat score, and multi-channel EEG. The recruitment period (2003–2012), spanned the introduction of hypothermia. Therefore the discriminative ability of the NRBC count for grade of encephalopathy could be compared in moderate/severely encephalopathic infants who did and did not receive hypothermia. Results: 86 infants with HIE were included in the study, 40 were mild, 26 moderate (14 normothermic, 12 hypothermic), and 18 severe (10 normothermic, 8 hypothermic). In the normothermic group, the NRBC count discriminated between mild and moderate/severe Sarnat scores (p=0.016), but not in the hypothermic group (p=0.297). This change was due to a decrease in NRBCs among infants with a moderate Sarnat score receiving hypothermia, This occurred despite these infants having a significantly worse 5 minute Apgar score (p<0.001) and background EEG at 6 hours (p=0.032) than their normothermic counterparts. Conclusion: This study has demonstrated that hypothermia can impact upon early post-natal blood biomarkers of HIE. We therefore advise caution in the use of these samples when studying novel diagnostic biomarkers for HIE in the hypothermic era.